2007
DOI: 10.1111/j.1365-3156.2007.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and inventory of the cytospecies and cytotypes of the Simulium damnosum complex (Diptera: Simuliidae) in relation to onchocerciasis

Abstract: SummaryWe provide an inventory of all named cytoforms of the Simulium damnosum complex (including those which are now considered invalid), along with all inversions that have been recorded (including synonyms and homonyms). There are 55 valid and distinct cytoforms known from the S. damnosum complex making it the largest sibling species complex of any vectors, and probably of any insect or other animal. All cytoforms are listed along with their fixed and diagnostic inversions and country distribution. There ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 45 publications
0
60
0
Order By: Relevance
“…Larvae were fixed in Carnoy's solution and kept at 4°C. Polytene chromosomes were prepared using standard methods (Dunbar 1972) and identified according to fixed diagnostic inversions (Post et al 2007;Boakye 1993).…”
Section: Methodsmentioning
confidence: 99%
“…Larvae were fixed in Carnoy's solution and kept at 4°C. Polytene chromosomes were prepared using standard methods (Dunbar 1972) and identified according to fixed diagnostic inversions (Post et al 2007;Boakye 1993).…”
Section: Methodsmentioning
confidence: 99%
“…This is likely to be especially relevant when studying S . damnosum s.l., a complex of sibling species composed of at least 55 morphologically indistinguishable cytospecies and cytoforms of unknown taxonomic status, each with unique ecological and behavioural traits [36, 37]. …”
Section: Introductionmentioning
confidence: 99%
“…crucians complex includes five sibling species . Nearly 30 years of chromosomal studies of African vectors have shown that Anopheles gambiae consists of seven or more sibling species , and Simulium damnosum consists of 55 sibling species and cytoforms (Post et al 2007), making it the largest species complex of any blood-feeding organisms. Hidden more deeply than sibling species are homosequential sibling species, which have the same banding sequences in their polytene chromosomes and virtually identical external morphologies (Bedo 1979).…”
Section: Numbers and Estimatesmentioning
confidence: 99%
“…Only a few of the ten or more sibling species of African biting midges in the Culicoides imicola complex have been implicated in the transmission of African horse sickness virus (Meiswinkel 1998, Mellor et al 2000. Of the 30 sibling species and cytoforms in the S. damnosum complex in northeastern Africa and East Africa, only 6 have been incriminated as vectors of the filarial parasite responsible for human onchocerciasis (Post et al 2007). Further, the vector species of the S. damnosum complex show differential susceptibilities and resistance to insecticides, requiring accurate identification to monitor the development and spread of resistance genes (Kurtak 1990).…”
Section: Societal Consequences Of Disregarding Biodiversitymentioning
confidence: 99%